2020
DOI: 10.1042/bsr20191908
|View full text |Cite
|
Sign up to set email alerts
|

miR-122/SIRT1 axis regulates chondrocyte extracellular matrix degradation in osteoarthritis

Abstract: Background/Aims: MicroRNAs (miRNAs) are involved in the pathogenesis of osteoarthritis (OA). The present study aimed to investigate the potential function of miR-122 in the development of OA and its potential molecular mechanisms. Methods: The expression of miR-122, silent information regulator 1 (SIRT1), collagen II, aggrecan, matrix metalloproteinase (MMP) 13 (MMP13) and ADAMTS4 in OA cartilage was detected by RT-qPCR. Target gene prediction and screening, luciferase reporter assay were used to verify downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…MicroRNA technology is a developing field; thus, there is variability in reported results, due in part to differences in cell models or tissue source. In contrast to our observation that miR-122 caused a marked decrease in MMP-13 in rArCs, a recent paper by Bai and colleagues reported that miR-122 increased MMP-13 expression and protein levels in SW1353 cells 35 . Both studies observed decreased expression of collagen II and aggrecan mRNAs.…”
Section: Discussioncontrasting
confidence: 99%
“…MicroRNA technology is a developing field; thus, there is variability in reported results, due in part to differences in cell models or tissue source. In contrast to our observation that miR-122 caused a marked decrease in MMP-13 in rArCs, a recent paper by Bai and colleagues reported that miR-122 increased MMP-13 expression and protein levels in SW1353 cells 35 . Both studies observed decreased expression of collagen II and aggrecan mRNAs.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been demonstrated that ECM can be degraded by metalloproteinases such as MMP-3 and MMP-9 in osteoarthritis. 27 Similarly, in our study, we found that treatment with roflumilast significantly reduced the production of MMP-3 and MMP-9 in IL-18-induced FLS. This finding indicates that roflumilast might have a potential effect in preventing the degradation of cartilage.…”
Section: Discussionsupporting
confidence: 82%
“…As mentioned above, miR-122 targets SIRT1, and this axis is reported to regulate chondrocyte extracellular matrix degradation in the cartilage of osteoarthritis [ 56 ]. The expression of miR-122 was increased in osteoarthritis cartilage compared to healthy controls, while SIRT1 expression was decreased.…”
Section: Major Mirnas In Hypoxic Signaling and Oxidative Stressmentioning
confidence: 99%
“…The expression of miR-122 was increased in osteoarthritis cartilage compared to healthy controls, while SIRT1 expression was decreased. The overexpression of miR-122 increased extracellular matrix catabolic factors, such as disintegrins and matrix metalloproteinases, and inhibited the expression of synthetic metabolic genes, such as collagen II and aggregating proteoglycan, partly via SIRT1 [ 56 ]. In the liver, miR-122 and SIRT6 negatively regulate each other’s expression, and they oppositely regulate a similar set of metabolic genes and fatty acid β-oxidation [ 57 ].…”
Section: Major Mirnas In Hypoxic Signaling and Oxidative Stressmentioning
confidence: 99%